REVITALISASI LIMA NILAI BUDAYA KERJA BERBASIS TELADAN HIDUP RASULULLAH SEBAGAI UPAYA MENCEGAH DAN MENGHILANGKAN PERILAKU KORUP (Telaah Konseptual di Lingkungan Kementerian Agama) - Arditya Prayogi; Muhammad Jauhari (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2021)
The birth of Five Work Cultures within the Ministry of Religion of the Republic of Indonesia, is to answer his desire to restore a good image and trust in the eyes of the public as evidenced by good performance after previously there were several cases of corruption that plagued him. The five work cultures include integrity, professionalism, innovation, responsibility, and exemplary. This article aims to describe how the concept of revitalizing these 5 work culture values, not only in terms of good government management or based on the embodiment of the vision and mission of institutions and leaders, but also based on the concept of Islam based on the Qur'an and As-Sunnah by making the Prophet Muhammad as a concrete role model. From the results of the study, it can be seen that conceptually the revitalization and implementation of five work cultures based on the example of the Prophet's life in the Ministry of Religion can be carried out with the discipline of application by relying on the best human example, namely the Prophet Muhammad, based on transcendental awareness.